Perubahan Konduktivitas Hidraulik dan Daya Hantar Listrik Tanah Akibat Pemberian Urea dan Bahan Organik pada Tanah Ultisol - Ida Suryani (Fapetrik-UMPAR, 2021)
This study aimed to determine the effect of urea added with organic matter in a high C/N (50-70) or low C/N (10-20) ratio on the hydraulic conductivity and electrical conductivity of Ultisol soil. The research was arranged in a Split Plot Design. The main plot is organic matter, ie, without organic matter, calopogonium leaves, and rice straw 1,275 x 10-8 kg/ha, equivalent to 15.3 g/pipe. Sub-plots were urea doses consisting of 0, 100, and 300 kg/ha, equivalent to 0 g/pipe, 0.0425 g/pipe, and 0.0825 g/pipe, respectively, applied to Ultisol soil. Sample of Ultisol soil was taken at a depth of 0 -120 m which were air-dried, then sifted, mixed with TSP, organic matter, and urea according to treatment. The sample was put in a PVC tube (pipe) with the bottom covered with fine gauze to hold the soil but still allow percolation. . Incubation was carried out for two weeks. Observations were made after the incubation period, including hydraulic conductivity and electrical conductivity. The application of organic matter and urea at a dose of 300 kg/ha can increase the electrical conductivity of the soil. Adding the main organic matter with a high C/N ratio (rice straw) increases the hydraulic conductivity. Electrical conductivity (EC) is a good indicator in explaining the dispersive effect of urea and the effect of flocculation of organic matter. High electrical conductivity always results in high hydraulic conductivity in Ultisol soils.